Regulation of Co-Ni/ MIL-101-C MOF reconstruction for enhanced deoxygenation reaction - Mohammed, Amera F.; Abdulkareem-Alsultan, G.; Obeas, Laith K.; Asikin-Mijan, N.; Samidin, Salma; Azri, Norsahida; Wan Khalit, Wan Nor Adira; Nassar, Maadh Fawzi; Lee, H.V.; Lai, Sin Yuan; Tan, Ming Yueh; Taufiq-Yap, Yun Hin (Elsevier, 2025)
This work investigated a mixed Co, Ni oxide supported-MOF catalyst for the selective deoxygenation of sustainable oil. Metal oxide decorated MIL-101 (Fe) (MOF) has emerged as cost-effective alternatives to noble metal-based catalysts for the oxygen removal by deoxygenation reaction in inert condition. The tuning effect of different Co and Ni loading ratios, along with varying MIL-101 (Fe) support loadings and operating temperatures under nitrogen conditions, was systematically studied. While the presence of Ni enhances deoxygenation activity, it also reduces MIL-101 (Fe) domains that are crucial for the reaction pathway. The reaction performance's condition effect was more pronounced with increasing Fe concentration in the supports. Remarkably, the deoxygenation activity decreased with increasing reaction temperatures. The optimized Co-Ni/MIL 101(Fe) catalyst (Co(6)-Ni(6)/MIL-(Fe)-C) exhibits exceptionally high acid and base site densities: 3246.82 and 1730.11 µmol/g), respectively, ranking it among the top-performing deoxygenation catalysts. It achieved a hydrocarbon yield of 98.84 % with an n-C15 selectivity of 85.43 %. This work introduces a novel active site structure and activation strategy for deoxygenation, highlighting the potential of rationally tuning the coordination environment of metal oxide sites to improve catalytic efficiency.